2020
DOI: 10.3390/vaccines8030537
|View full text |Cite
|
Sign up to set email alerts
|

Electroporation as the Immunotherapy Strategy for Cancer in Veterinary Medicine: State of the Art in Latin America

Abstract: Electroporation is a technology that increases cell membrane permeability by the application of electric pulses. Electrochemotherapy (ECT), the best-known application of electroporation, is a very effective local treatment for tumors of any histology in human and veterinary medicine. It induces a local yet robust immune response that is responsible for its high effectiveness. Gene electrotransfer (GET), used in research to produce a systemic immune response against cancer, is another electroporation-based trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 125 publications
0
21
0
2
Order By: Relevance
“…Various delivery approaches may follow different routes of antigen delivery depending on the treatment needs. Electroporation techniques such as electrochemotherapy (ECT) and gene electrotransfer (GET) can deliver antigens directly into tumors or tumor sites to generate robust immune responses [12]. Similarly, regional delivery of ICBs has shown promising results in animal models of metastatic disease [8].…”
Section: Recent Developments In Prophylactic and Therapeutic Cancer Vaccinesmentioning
confidence: 99%
“…Various delivery approaches may follow different routes of antigen delivery depending on the treatment needs. Electroporation techniques such as electrochemotherapy (ECT) and gene electrotransfer (GET) can deliver antigens directly into tumors or tumor sites to generate robust immune responses [12]. Similarly, regional delivery of ICBs has shown promising results in animal models of metastatic disease [8].…”
Section: Recent Developments In Prophylactic and Therapeutic Cancer Vaccinesmentioning
confidence: 99%
“…An electrical pulse generator, CliniporatorTM (IGEA s.r.l., Carpi, Italy), was used to deliver electrical pulses through either plate, hexagonal, or needle electrodes. The selection of electrode type, voltage, duration, and frequency of the electrical pulses was based on ECT (23,35,(48)(49)(50)(51)(52) and GET studies (25-28, 33) (Table 2).…”
Section: Ect Combined With Get Pil-12mentioning
confidence: 99%
“…Electrochemotherapy (ECT) and/or gene electrotransfer of plasmid DNA encoding interleukin-12 (GET pIL-12) are effective treatments for cutaneous, subcutaneous and maxillofacial tumors in dogs ( 25 41 ), superficial cell carcinoma in cats ( 42 ), cutaneous tumors in ferrets ( 43 ) and sarcoid tumors in horses ( 44 , 45 ). Several preclinical ( 46 49 ) and clinical studies in veterinary patients ( 26 28 , 33 , 36 , 50 ) have shown that the effect of ECT is potentiated by GET pIL-12, and ECT has become an established standard of care for a variety of human cancers: cutaneous and subcutaneous tumors, including melanoma, squamous cell carcinoma, basal cell carcinoma, and other metastases ( 51 58 ); hepatocellular carcinoma and colorectal liver metastases ( 59 63 ); pancreatic neoplasia ( 64 66 ); and others. A portion of the antitumor efficacy of electroporation (EP)-based therapies arises from the effect of EP on the vasculature of the treated tumor, inducing a local blood flow effect, namely, “vascular lock,” i.e., small blood vessel vasoconstriction and increased wall permeabilization ( 67 – 74 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this safe and efficient non-viral gene delivery approach, the permeability of cell membrane is increased after electroporation of cells or tissues, which enables the introduction of different nucleic acids. Several different electroporation systems exist for delivery of genetic material, but the working principle is the same [ 18 , 19 , 20 , 21 , 22 ]. In the case of pDNA, after application of controlled electric pulses to cells or tissues, a pDNA-membrane complex is formed on the membrane facing the cathode, then this complex enters the cells via endocytosis [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%